Hepatocellular carcinoma: microstructure and expression features of hepatocyte marker, alphafetoprotein, cytokeratins 7 and 20 - V. A. Tumanskiy; M. D. Zubko (Patologìâ)
V. A. Tumanskiy, M. D. Zubko Aims. In order to determine the microscopic features and expression level of HepРar-1, AFP, CK7, CK20 by the cells of hepatocellular carcinoma histopathological, histochemical and immunohistochemical study of 53 liver biopsies from patients with hepatocellular carcinoma was conducted. Methods and results. The photo digital morphometry was used and area of immunopositive cells was calculated. In 92.45% of cases the cytoplasmic expression of HepPar was established. The area of immunopositive cells was 49.35±25.45%. 81.13% of patients with hepatocellular carcinoma had the cytoplasmic and nuclear expression of α- fetoprotein. The area of AFP-immunopositive cells was 37.25±15.47% on the average. There was a direct weak connection between the expression level of HepPar-1 and AFP. CK7 expression was noted in 37.74% of cases and CK20 expression was noted in 30.13% of cases of HCC. CK7+ and CK20+ cells are distributed in the form of focal clusters and take area of 21.08±5.19% and 29.35±17.31% respectively. There was direct medium strength connection between the expression level of AFP and СК7, AFP and СК20 by the tumor cells. There was strong direct correlation between the level of expression of HepPar-1 and CК7, HepPar-1 and CК20.